'Hi-Fi AFM': high-speed contact mode atomic force microscopy with optical pickups. (4th September 2018) - Russell-Pavier, F S; Picco, L; Day, J C C; Shatil, N R; Yacoot, A; Payton, O D
Abstract: High-speed atomic force microscopy (HS-AFM) is a powerful emerging technique used to gain insight into real-time nanoscale dynamics and phenomena across the sciences. By performing measurements of material properties, abundancy counting and dimensional analysis, it enables a new generation of discoveries at the atomic scale. Here, we demonstrate the use of an optical pickup unit (OPU) typically found in PCs, hi-fis and games consoles worldwide, as a vertical detection system within in a HS-AFM operated in contact mode. The OPU displacement performance is compared to that of a commercially available laser Doppler vibrometer with ±15 pm resolution. Sub-nanometre sensitivity is achieved with an OPU, presented via the identification of two resonant modes of a cantilever stimulated by ambient thermal excitation. To demonstrate the large dynamic range of the sensor at fast scan-speeds, surface profiles with step heights in excess of 100 nm and surface textures less than 10 nm were collected using a custom OPU-based HS-AFM. The high-fidelity measurements are extended to visible length scales in short timescales by imaging areas of up to 200 µ m 2 area at a pixel rate of 2 megapixels s −1, tip velocity of 10 mm s −1 and area rate of 25 µ m 2 s −1 .